Routine Preoperative Frailty Assessment Predicts Postoperative Complication in PCNL Surgery - Alfryan Janardhana; Suparno Adi Santika (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2023)
Objectives. Frailty is an assessment of functional status related to postoperative outcome. This observational study aims to determine differences in the frailty status of patients undergoing Percutaneous Nephrolithotomy (PCNL) with the incidence of postoperative complications.Methods. This is a retrospective cohort study design conducted at a tertiary referral hospital in Jember with the patient's medical record as the source of data. The frailty status is evaluated using Clinical Frailty Scale(CFS) which are categorized into frailty and non-frailty. The outcomes of this study were perioperative and the incidence of postoperative complications which included estimated blood loss, fever, sepsis, Intensive Care Unit (ICU) admission, Deep Vein Thrombosis (DVT), and postoperative.Results. Of the 24 patients who were screened, 7 patients with frailty status and 17 patients with non-frailty status before PCNL were performed. Patients with frailty status occur at an older age with a significance value of 0.001 and have a risk of postoperative complications such as fever, length of stay (LOS), sepsis, ICU admission and higher blood transfusion compared to non-frailty patients. The result of the comparison test from length of stay showed a significance of <0.001 (p<0.05). The perioperative events did not have a significant relationship with frailty status.Conclusions. Assessment of frailty status prior to PCNL is very useful for predicting the incidence of postoperative complications. Risks include fever, sepsis, length of stay, ICU care and blood transfusion are higher in patients with frailty status.